The Effect of Concentration and Application Interval of Plant Growth-Promoting Rhizobacteria (PGPR) from Thorny Bamboo Roots (Bambusa blumeana) on the Growth and Yield of Chili Pepper (Capsicum frutescens L.) - Lisna P.J. Tamba; Cicik Suriani (Program Magister Ilmu Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2025)
The steady demand for chili pepper throughout the year encourages farmers to plant continuously without considering environmental factors, thereby reducing chili pepper production. This decline is caused by low soil fertility due to excessive use of chemical fertilizers. One environmentally friendly approach is the use of Plant Growth Promoting Rhizobacteria (PGPR) Thorny Bamboo Roots (Bambusa blumeana). This study aims to determine the effect of PGPR concentration and application interval, as well as their interaction, on the growth and yield of chili pepper plants. The study used a two-factor Randomized Block Design (RBD), namely concentration (K0: 0 ml/L, K1: 10 ml/L, K2: 20 ml/L, K3: 30 ml/L, K4: 40 ml/L) and time interval (I1: once every 7 days, I2: once every 14 days). The research data were analyzed using ANOVA and then continued with the BNT test. The results showed that the PGPR concentration had a significant effect on all parameters, namely plant height, number of leaves, stem diameter, number of flowers, number of fruits, and wet weight, while the time interval only had a significant effect on stem diameter, and the interaction between the two had no significant effect on all treatments. A concentration of 40 ml/L (K4) was the best concentration, with an average plant height of 63.66 cm, number of leaves of 23.66, stem diameter of 12.86 mm, number of flowers of 16.66, number of fruits of 17.16, and wet weight of 20.73 grams. The 14-day interval (I2) was the optimal interval for stem diameter, with an average of 4.58 mm. Keyword: Thorny bamboo, chili pepper, time interval, concentration, PGPR